Iatrogenic tension pneumocephalus complication of osteoradionecrosis in the treatment of nasopharyngeal carcinoma. A case report and critical literature review - Isidro Miguel Martín Pérez; Sebastián Eustaquio Martín Pérez; Adolfo Vérgez Muñoz; Nart Keituqwa Yáñez; María Carmen Dolado Correa; Carolina Rodríguez González; Fidel Rodríguez Hernández (Brazilian Journal of Oncology)
Nasopharyngeal carcinoma typically originates in the fossa of Rosenmüller within the mucosal epithelium directly underlying the lymphatic tissue, and commonly presents clinically with symptoms such as headache, dizziness, and rhinorrhea. In this case study, we describe a 61-year-old man diagnosed with nasopharyngeal carcinoma who underwent radiation therapy with a total dose of 50 Gy administered at a rate of 2 Gy per day, along with chemotherapy consisting of cisplatin at a dose of 100 mg/m2. Surgical intervention was deemed unsuitable due to the size of the tumors. Five months later, the patient developed a tension pneumocephalus due to a clival fistula “corking effect,” which resulted in the infiltration of air bubbles into the brain and culminating in his death 2 weeks after admission to the intensive care unit.